Lithium tetrafluoroborate catalyzed highly efficient inter- and intramolecular aza-Michael addition with aromatic amines - Lad, Uday P.; Kulkarni, M. A.; Desai, Uday V.; Wadgaonkar, P. P. (Comptes Rendus Chimie, 2011)
Lithium tetrafluoroborate has been demonstrated for the first time to be an efficient catalyst in intermolecular aza-Michael addition aromatic amines to electron deficient alkenes. Suitability of the same catalyst in intramolecular aza-Michael addition leading 2-aryl-2,3-dihydroquinolin-4(1H) ones has also been described. (C) 2011 Published by Elsevier Masson SAS on behalf of Academie des sciences.
Keywords: 2-aryl-2; 3-dihydroquinolin-(4H)-1-ones; Anilines; Lithium tetrafluoroborate; Michael addition

Diethylamine: a smart organocatalyst in eco-safe and diastereoselective synthesis of medicinally privileged 2-amino-4H-chromenes at ambient temperature - Kulkarni, Makarand A.; Pandit, Kapil S.; Desai, Uday V.; Lad, Uday P.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
Diethylamine has been demonstrated to be an efficient organocatalyst in the diastereoselective synthesis of Bcl-2 protein antagonist (HA-14-1) and of its structural analogues by one-pot condensation between salicylaldehyde and three different C-H acids, viz, ethyl cyanoacetate, phenylsulfonyl acetonitrile, and malononitrile. Easy commercial availability of the catalyst at extremely low cost and avoidance of conventional work-up as well as purification procedures qualifies this scalable protocol for a ``near-ideal synthesis''. (c) 2013 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: 2-amino-4H-chromenes; Active methylene compounds (C-H acids); diethylamine; multicomponent reactions; organocatalyst

Mechanistic approach for expeditious and solvent-free synthesis of alpha-hydroxy phosphonates using potassium phosphate as catalyst - Kulkarni, Makarand A.; Lad, Uday P.; Desai, Uday V.; Mitragotri, Satish D.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2013)
An extremely simple, high yielding, highly rapid and solvent-free protocol has been described for hydrophosphylation of aldehydes using potassium phosphate as catalyst. Easy commercial availability of the reusable catalyst, operational simplicity at ambient temperature and avoidance of conventional work-up as well as purification procedure makes this solvent-free protocol a near-ideal synthesis. (C) 2012 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.
Keywords: alpha-hydroxy phosphonates; Hydrophosphylation; Potassium phosphate; Solvent-free